The representation of inherent properties. Issue 5 (October 2014) - Prasada, Sandeep
Abstract Research on the representation of generic knowledge suggests that inherent properties can have either a principled or a causal connection to a kind. The type of connection determines whether the outcome of the storytelling process will include intuitions of inevitability and a normative dimension and whether it will ground causal explanations.